Isomorphic metal malonates with N-aminoguanidine: MCo2O4 (M = Ni & Zn) nanoparticle synthesis via a (AmgH)2[M1/3Co2/3(mal)2(H2O)2] precursor solid solution. (3rd November 2015) - Selvakumar, Rajendran; Geib, Steven J.; Premkumar, Thathan; Vairam, Sundararajan; Govindarajan, Subbiah
Abstract : Divalent metal complexes of malonate with aminoguanidine and their solid solutions are prepared. The solid solutions are used as precursors for nanosized spinel oxides. Abstract : Divalent metal complexes of malonate with aminoguanidine possessing (AmgH)2 [M(mal)2 (H2 O)2 ] [M = Co (1 ), Ni (2 ) or Zn (3 ); mal = malonate anion and AmgH = aminoguanidinium cation] stoichiometry and their solid solutions, (AmgH)2 [Ni0.5 Co0.5 (mal)2 (H2 O)2 ] (4 ) and (AmgH)2 [M1/3 Co2/3 (mal)2 (H2 O)2 ] [where M = Ni (5 ) or Zn(6 )], were prepared and characterized by analytical, thermal and powder X-ray diffraction studies. The crystal and molecular structures of both cobalt and nickel compounds were isomorphic, crystallizing in the triclinic space group P 1̄. The complexes exhibit similar modes of endo-followed by exothermic decomposition to produce respective metal oxides below 550 °C. Metal cobaltites, MCo2 O4 where M = Ni and Zn, were obtained from the above solid solutions as decomposition residues by heating at 600, 700 and 800 °C in a silica crucible for 3 h. Spinel oxides nanoparticles were characterized by infrared spectra, powder X-ray diffraction patterns, scanning electron microscope coupled with energy dispersive X-ray analysis and transmission electron microscope studies.